Impact of saline sprouting on antioxidant properties and bioactive compounds in chia seeds - Dordevic Dani; Hrachovska Jana; Dordevic Simona; Kushkevych Ivan (Open Life Sciences)
The consumption of chia seeds has surged in recent years, primarily due to their beneficial chemical composition and health effects. Sprouting chia seeds can enhance the content of essential nutrients, including antioxidants and vitamins. The study investigates the impact of sprouting on the bioactive compounds and antioxidant activity of chia seeds under both favorable and stressful conditions. Chia seeds were sprouted in tap water, distilled water, and varying concentrations of seawater. The parameters analyzed included antioxidant activity, the reducing capacity of antioxidants, total polyphenol content, flavonoid content, and phenolic profile. Results indicated that sprouting significantly influences antioxidant activity in seeds sprouted in tap and distilled water, with a decrease observed only in the 2,2′-azinobis(3-ethyl-2,3-dihydrobenzothiazol-6-sulfonate) method for distilled water. Additionally, sprouting in both water types led to a statistically significant increase (p < 0.05) in reducing capacity and total polyphenol content. Under high salinity conditions, sprouting in 100% seawater resulted in a significant increase (p < 0.05) in antioxidant activity, reducing capacity, and total polyphenol content. These findings suggest that sprouting chia seeds, particularly under saline conditions, could enhance their nutritional profile, presenting potential applications in the food and nutrition industry and indicating possibilities for ecological cultivation.